Experimental Study on Stiffness Degradation and Liquefaction Characteristics of Marine Sand in the East Nan-Ao Area in Guangdong Province, China - Fayun Liang; Zewang Zhang; Chen Wang; Xiaoqiang Gu; Yifeng Lin; Wei Yang (Journal of Marine Science and Engineering, 2021)
Offshore wind power, as an efficient renewable energy source, is being vigorously developed nowadays. However, the liquefaction of marine sand due to earthquakes brings potential safety hazards to the wind turbine structures. In this study, a series of resonant column and undrained cyclic triaxial tests were carried out to investigate the stiffness degradation and liquefaction characteristics of marine sand in the offshore wind farm at the East Nan-ao area in Guangdong Province (China). Results show that the confining pressure increases the shear modulus of sand and restrains the nonlinearity of modulus. The liquefaction resistance of soils significantly increases with the increase of relative density. The effect of particle size on the liquefaction resistance is related to the cyclic shear stress ratio. The additional pressure induced by the presence of the wind turbine structure enlarges the energy required for shallow soil liquefaction. Besides, a model for predicting shear modulus and another modified model based on Seed’s pore pressure development model have been established, which can efficiently fit the dynamic shear modulus and the generation of excess pore water pressures in the tests, respectively.